Innovative Human Resource Management Strategies in the Era of Digital Transformation - Bahiroh, Eloh; Imron, Ali (Penelitian dan Pengembangan Ilmu, 2024)
In the era of digital transformation, innovative human resource management (HR) strategies are very important for organizations to overcome the challenges faced in adopting digital technology. This research conducted a thorough literature review to explore key factors associated with innovative HR strategies in the era of digital transformation. The results of the literature review show that adapting technology in HR, increasing employee digital competence, talent management, and effective performance measurement are important aspects in achieving organizational success in this digital era. Apart from that, organizational adaptation to new phenomena also demands adaptive HR management strategies. This research also proposes a hypothesis that links these various factors to an organization's success in facing digital transformation. It is hoped that this research can provide valuable insight for organizations in developing relevant and effective HR strategies in facing the challenges of the digital era.